DEVELOPING AN ENGLISH INSTRUCTIONAL MATERIAL FOR BRIDGING COURSE PROGRAM (English Education Journal, 2012)
Studi ini mencoba untuk mencari tahu materi apa yang dibutuhkan pada siswa kelas 7 pada program Bridging Course di SMPN 2 Magelang, bagaimana “Good Start for Beginners” efektif dan sesuai. Berdasarkan masalah yang ada, penelitian ini bertujuan untuk mengembangkan materi instruksional pada program bridging course oleh siswa dan guru. Penelitian ini menggunakan pendekatan Research & Development (R&D). Peneliti menggunakan semua langkah yang diajukan oleh Hyland (2003:83). Pertama, survey, berdasarkan KTSP SMP RSBI Negeri 2 Magelang dilakukan kepada siswa SMP kelas VII. Kedua, peneliti mengembangkan materi. Ketiga, validasi dilakukan untuk penyesuaian. Sampai akhirnya siswa menyukai materi tersebut. Pencapaian siswa setelah menggunakan “Good Start for Beginners” terbilang baik. Rata-rata skor siswa 80,42 yang mengindikasikan bahwa buku “Good Start for Beginners”  efektif dan sesuai untuk digunakan.This study is an attempt to find out what kinds of English materials are needed by grade seven students in the bridging course program of SMPN 2 Magelang, how the “Good Start for Beginners” is developed, why a validation is needed, and whether the “Good Start for Beginners”  is effective and appropriate. Based on the research problems, this study is aimed to develop an English instructional material for bridging course program used by teachers and students. The approach used in this study is Research and Development (R&D). I used all of the steps proposed by Hyland (2003:83). First, a survey was done by mapping the needs of the students based on KTSP of SMP RSBI Negeri 2 Magelang for grade seven of Junior High School. Second, I developed material. Third, a validation is really needed for adjusting. Finally, the students gave the good opinions about the book. All of them liked the material very much. The students’ achievement after being taught by using “Good Start for Beginners” is good.  The total average of students’ achievement on four language skills was 80, 42. It implies that “Good Start for Beginners” teachers and students textbook are effective and appropriate to use.